Pengaruh Lokasi, Pendapatan Konsumen, Harga Rumah Dan Selera Terhadap Keputusan Pembelian Rumah Bersubsidi Di Kabupaten Manokwari - Noviani Walalayo; Rumas Alma Yap; Lillyani M. Orisu (JFRES Journal of Fiscal and Regional Economy Studies, 2020)
This study aims to determine the influence of location, consumer income, house prices, appetite for subsidized home purchase decisions in Manokwari Regency. The variables in this study are Location, Consumer Income, House Price and Taste. This study uses primary data and secondary data. Primary data obtained through questionnaires and secondary data obtained through agencies related to this study, the analysis method used is to use multiple linear regression models using the SPSS Statistic 16 program. The results of the partial study (t test) Location, Kosumen Income, House Prices and tastes had a positive and significant effect on the decision to purchase subsidized homes in Manokwari Regency. But together (simultaneously) variable locations, consumer income, house prices and tastes significantly influenced purchasing decisions at a confidence level of 95 percent.